Intratumor microbiota as a novel potential prognostic indicator in mesothelioma - Pentimalli, Francesca; Krstic-Demonacos, Marija; Costa, Caterina; Mutti, Luciano; Bakker, Emyr Yosef (Frontiers in Immunology, 2023)
Despite increased attention on immunotherapy, primarily immune checkpoint blockade, as a therapeutic approach for mesothelioma (MMe), its efficacy and tolerability remain questioned. One potential explanation for different responses of cancer to immunotherapy is the gut and intratumour microbiota; however, the microbiota remains a facet of MMe that is relatively underexplored. This perspectives article highlights the cancer intratumour microbiota as a potential novel prognostic indicator in MMe. Based on analysis of TCGA data from 86 MMe patients and decontamination analysis, 107 genera signatures were significantly associated with patient survival (positively or negatively) when patients were divided into “Low Survivors” and “High Survivors” groups. Comparison of clinical characteristics between the two groups demonstrate that histological subtype was significantly different, with epithelioid histology more common in the “High Survivors” group and biphasic more common in the “Low Survivors” group. Of the 107 genera signatures identified, 27 had published articles related to cancer, whilst only one genus (Klebsiella) had published articles relating to MMe. Functional annotation analysis of the differentially expressed genes between the two groups highlighted fatty acid metabolism as the most enriched term in the “High Survivors” group, whilst for “Low Survivors” the enriched terms primarily related to cell division and cell cycle. Linking these ideas and findings together is that the microbiome is known to influence, and be influenced by, lipid metabolism. Finally, to validate the independent prognostic value of the microbiome, multiple linear regression modelling as well as Cox proportional hazards modelling were employed, with both approaches demonstrating that the microbiome was a better prognostic indicator than patient age or stage of the cancer. The findings presented herein, alongside the very limited literature resulting from scoping searches to validate the genera identified, highlight the microbiome and microbiota as a potentially rich source of fundamental analysis and prognostic value. Further in vitro studies are needed to elucidate the molecular mechanisms and functional links that may lead to altered survival.